SELF-CARE TRAINING FOR SANTRI AS AN EFFORT TO PREVENT SCABIES IN PESANTREN - Khamida; Fitriasari, Andikawati; Widyaswari, Meidyta Sinantryana (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Islamic boarding schools in Indonesia have classic problems related to the health of students, one of which is common in Islamic boarding schools and identical to the lives of students, is scabies. This community service activity was carried out at the As Syafiiyah Islamic boarding school to provide solutions to the problems of the As Syafiiyah Islamic boarding school community by providing education, training as well and mentoring Islamic boarding school health cadres in preventing scabies. This activity is carried out by providing education, training, and assistance to students and poskestren cadres about